An unusual case of fistula formation and thrombosis between arteriovenous graft and a native vein - Kim, Young Sub (Kidney Res Clin Pract, 2016)
Arteriovenous graft for hemodialysis vascular access is a widely used technique with many advantages. However, it has crucial complications with graft thrombosis and infection. We recently experienced an unusual case of arteriovenous graft complication involving graft thrombosis related to fistula formation between the graft and the natural vein with infection. We diagnosed this condition using Doppler ultrasound and computed tomography angiography. Successful surgical treatment including partial graft excision and creation of a secondary arteriovenous fistula using an inadvertently dilated cephalic vein was performed. The dialysis unit staff should keep this condition in mind and try to prevent this complication.